Center-Pivot-Irrigated Forage Sorghum Silage Cost-Return Budget in Western Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Holman, John; Haag, Lucas (My University, 2014)
This publication estimates the costs and returns associated with center-pivot-irrigated forage sorghum put up as silage in western Kansas.
MF998_2014_02
Keywords: MF998; Economics; Crops; MF